Exploring Suicidal Ideation in College Students - Melanie Mann; Bonnie Ahn; Lolita Boykin (Undergraduate Research Journal for the Human Sciences, 2016)
The goal of this study is to provide insight into the challenges that college students with suicidal thoughts face as a marginalized group and to yield information that will expand the existing body of knowledge regarding this topic. The study was based on the collective experiences of three college students and the language constructed by them during in-depth interviews. Results suggest that these interviewees experienced pain and suffering over a prolonged period of time inspiring thoughts of suicide. All participants stated that they did not want to be thought of negatively or misunderstood, so they didn’t talk about it on campus or to their parents. It is crucial for the general college student population and mental health professionals to recognize and validate the struggles of these students, particularly during crisis. Advocacy in colleges and universities will take on special importance as more students with special needs, particularly those with mental health issues make the transition from secondary to postsecondary education. The experiences of these three participants are important and meaningful; however they may not necessarily be representative of the greater populations.
Keywords: Suicidal; Ideation